Peningkatan Keterampilan Proses Sains Melalui Model Inkuiri Terbimbing bagi Siswa SD Negeri 1 Pingit Kabupaten Temanggung Jawa Tengah - Nasiroh, Dinda (Jurnal Paedagogy, 2021)
This study aims to improve science process skills through a guided inquiry model for Grade IV students at SD Negeri 1 Pingit. This research method is classroom action research which consists of two cycles with 3 meetings. The research design follows the research phase which refers to the modification of the Kemmis and Mc. Taggart, namely 1) action planning, 2) action implementation, 3) observation, and 4) reflection. The data collection technique used is the observation of teacher activity, student activity and observation of science process skills. The data analysis technique of this research used descriptive analysis. The results of this study indicate that there is an increase in science process skills from cycle I and cycle II. The increase was proven from the analysis of science process skills in the first cycle with an average of 73.21 with a completeness of 78.95%. In cycle II, science process skills obtained an average of 82.47 with 100% completeness. This shows that the guided inquiry model can improve the science process skills of fourth graders at SD Negeri 1 Pingit for the 2020/2021 academic year.